2017
DOI: 10.1021/acs.inorgchem.7b01075
|View full text |Cite
|
Sign up to set email alerts
|

Blue-to-Green Emitting Neutral Ir(III) Complexes Bearing Pentafluorosulfanyl Groups: A Combined Experimental and Theoretical Study

Abstract: A structure–property relationship study of neutral heteroleptic (1 and 2, [Ir(C∧N)2(L∧X)]) and homoleptic (3 and 4, fac-[Ir(C∧N)3]) Ir(III) complexes (where L∧X = anionic 2,2,6,6-tetramethylheptane-3,5-dionato-κO3,κO6 (thd) and C∧N = a cyclometalating ligand bearing a pentafluorosulfanyl (−SF5) electron-withdrawing group (EWG) at the C4 (HL1) and C3 (HL2) positions of the phenyl moiety) is presented. These complexes have been fully structurally characterized, including by single-crystal X-ray diffraction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Three issues arise when employing this strategy. The first is that the electrochemical stability of fluoro substituents, the most popular electron‐withdrawing substituent, such as in the widely studied FIrpic [iridium(III)bis(4,6‐difluopyridinato‐N,C 2′ )picolinate] sky blue emitter, is poor, translating to greatly reduced device stability; while the use of other more strongly electron‐withdrawing substituents do not necessarily translate into bluer‐emitting complexes, despite deepening the highest occupied molecular orbital (HOMO) of the compound . The second is that as the energy of the emissive triplet state increases, nonradiative recombination via thermally accessible metal‐centered excited states becomes increasingly problematic, leading to emitter degradation .…”
Section: Redox Potentials Of 1 and 2 And Reference Complexes R1 R2 mentioning
confidence: 99%
“…Three issues arise when employing this strategy. The first is that the electrochemical stability of fluoro substituents, the most popular electron‐withdrawing substituent, such as in the widely studied FIrpic [iridium(III)bis(4,6‐difluopyridinato‐N,C 2′ )picolinate] sky blue emitter, is poor, translating to greatly reduced device stability; while the use of other more strongly electron‐withdrawing substituents do not necessarily translate into bluer‐emitting complexes, despite deepening the highest occupied molecular orbital (HOMO) of the compound . The second is that as the energy of the emissive triplet state increases, nonradiative recombination via thermally accessible metal‐centered excited states becomes increasingly problematic, leading to emitter degradation .…”
Section: Redox Potentials Of 1 and 2 And Reference Complexes R1 R2 mentioning
confidence: 99%
“…Considering the wide range of trifluoromethylated compounds of interest, the synthesis of their SF 5 -analogs has become a trend to increase the properties of these valuable molecules [ 9 ]. Due to the unique properties, the SF 5 group has been used in various fields of chemistry, including pharmaceuticals [ 10 16 ], agrochemistry [ 17 – 20 ], and materials sciences [ 21 26 ]. The applications have, however, been limited by the poor synthetic accessibility of SF 5 -containing molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For the D1 R series, it was observed that in general the introduction of the substituents induced a small hypsochromic shift on their absorption spectra (Figure b). This effect is due to a greater HOMO stabilization when compared to the LUMO stabilization . Particularly, D1h in the external chemical environment has exhibited the largest HOMO–LUMO gap of about 4.79 eV ( λ max = 276 nm, Figures S11 and S12).…”
Section: Resultsmentioning
confidence: 98%